Communicative Grammar: Analysis of the Words "How Ever" In the Lob Corpus - Rodríguez R. Elizabeth (Universidad Nacional de Colombia, 2000)
The present analysis of the word however, as a practical rather than theoretical activity, draws on insights from everyday talk and information from both native speakers of English and EFL students as well as from the invaluable help of mainly "A Communicative Grammar of English"1 , "A Grammar of Contemporary English"2 and above all, "A Comprehensive Grammar of the English Language" .3 The emphasis in this analysis is, therefore, on the meanings and uses of the word however (semantics and pragmatics) rather than on its syntax. Nevertheless, this aspect of the language underlying however is also taken into consideration.